Causes and Remedies for Suicide in Adolescents and Youth: A Critical Analysis: Exploring the Risk Factors and Strategies for Suicide Prevention in Adolescents and Youth (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Suicide happens more often in older individuals than in younger ones, but it is globally one of the main cause of death in late and late infancy. This not only leads to a clear loss of many young people but also has a relational and socio-economic influence that is destructive. Suicide in young adults is a critical concern from the viewpoint of public mental wellbeing. Therefore, we need a clear understanding of the contributing factors that lead to adolescent suicide. This mini-exploration offers a concise description of the key risk factors for children and young people of late school age as defined by clinical studies. Main risk factors identified included behavioral issues, prior attempts at suicide, unique personality traits, genetic loading and family mechanisms in association with psychosocial stressors, exposure to images of motivation and the availability of suicide strategies. Further unraveling and understanding of the dynamic interplay of these variables are of immense significance in the creation of successful suicide reduction strategies.